DEVELOPMENT OF THE ANALYTICAL METHOD TO DETERMINE ACRYLAMIDE IN STRAW POTATO: VALIDATION AND DETERMINATION - Pinheiro, Maria Clara de Oliveira; Abrantes, Shirley de Mello Pereira (Boletim do Centro de Pesquisa de Processamento de Alimentos, 2020)
Acrylamide is not naturally present in food, being one of the mechanisms of its formation in foods based on the Maillard reaction between amino acids, especially asparagine and reducing sugars when subjected to high temperatures. Foods rich in these two precursors are derived mainly from products of plant origin such as potatoes and cereals. The formation of acrylamide is observed in the cooking, frying, roasting or carbohydrate-rich foods roasting with temperatures above 120°C and tends to increase with cooking time and with raising the temperature. According to the International Agency for Research on Cancer (IARC), acrylamide is classified as a likely carcinogenic substance in humans (group 2A) and, furthermore, can be toxic to the nervous and reproductive systems of men and animals at certain doses. The World Health Organization (WHO) has established a tolerable daily intake of acrylamide of 12 μg kg -1 body weight (BW) / day. Numerous studies around the world have facilitated the emergence of more specific research, where it is possible to dedicate to a food and to evaluate the exposure to acrylamide in a certain context. The objective of this study is to validate an analytical method by high performance liquid chromatography (HPLC) for the evaluation and quantification of the presence of acrylamide in straw - type fried potatoes marketed in the city of Rio de Janeiro. The analytical method used for the detection and quantification of acrylamide in straw potato was high performance liquid chromatography with ultraviolet detection. The validation of the method relied on linearity tests, repeatability, matrix effect, intermediate precision, determination of the limit of quantification and limit of detection. The content of acrylamide found in the potatoes varied from 134.27 μg / kg to 427.42 μg / kg. The effective evaluation of the acrylamide levels found in different foods consumed by the Brazilian population tends to generate data that contribute to public policies that are strengthened and have a foundation to interfere with and determine that the manufacturing of processed foods is carried out in a way that decreases the content of this poisoning contaminant.